STRATEGI PROBING PROMPTING DALAM UPAYA MENGONSTRUKSI PEMAHAMAN MAHASISWA TERHADAP FUNGSI DUA VARIABEL - Hapizah; Somakim; M. Yusup (Mathematics Education Journal, 2019)
The article describes about validation of teaching material in which some probing-prompting questions were created to construct students’ understanding about function of two variables. This research is a design research and its type is development study. Data was collected by walk-through and documentation methods. The research produced the structure of questions to construct students’ understanding about some topics which are domain, range, contour plot or contour maps, surface, and level of curve of function of two variables, and the teaching material is supplemented by Geogebra application. The questions about topics of domain and range material are probed by topics of domain and range of function of one variable. The teaching material is valid.